2001
DOI: 10.1034/j.1399-5448.2001.20408.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of serum collagen type IV in children with type 1 (insulin-dependent) diabetes mellitus - a longitudinal study

Abstract: The basement membrane is a major focus of scientific interest because of its role in a variety of diseases. In diabetes mellitus, a thickening of the capillary basement membrane results in microangiopathic lesions. To monitor the metabolism of the basement membrane protein collagen type IV (CIV) in diabetes mellitus, serum levels of CIV were measured using an enzyme-linked immunosorbent assay (ELISA) method in 28 children with type 1 diabetes mellitus over a period of 6 years. These values were compared to ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
0
6
0
1
Order By: Relevance
“…Collagen IV is a major matrix protein of the basement membranes, and elevated serum and urine levels have been associated with diabetic microangiopathic complications, especially DN [ 60 64 ]. Lee et al [ 59 ] found that plasma levels of 7S-collagen, a collagen IV domain resistant to various proteases, are elevated in DR and DN and that its levels increased with the severity of both diseases.…”
Section: Biomarkers Of Basement Membrane and Extracellular Matrix mentioning
confidence: 99%
“…Collagen IV is a major matrix protein of the basement membranes, and elevated serum and urine levels have been associated with diabetic microangiopathic complications, especially DN [ 60 64 ]. Lee et al [ 59 ] found that plasma levels of 7S-collagen, a collagen IV domain resistant to various proteases, are elevated in DR and DN and that its levels increased with the severity of both diseases.…”
Section: Biomarkers Of Basement Membrane and Extracellular Matrix mentioning
confidence: 99%
“…Increased levels of autoantibodies against collagen type IV have been associated with diabetes and development of microangiopathy [14] and have also been reported in patients with systemic vasculitis and Crohn's disease [13], [15]. Moreover, autoantibodies against collagen type IV have been detected in children with type 1 diabetes and hypertension [16], [17].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, an important factor for the development of diabetic vascular complications is the alteration in the structure of the vascular proteins. Peptides derived from such processes have been found in the circulation (Nicoloff et al, 2000a(Nicoloff et al, , 2001 and they are reasoned to be a stimulus for increased production of autoantibodies. A variety of autoantibodies have been documented in diabetes and include insulin autoantibodies, GAD-autoantibodies, tyrosine phosphatase IA2-autoantibodies, islet cell-autoantibodies, (Verge et al, 1998) elastin autoantibodies (Nicoloff et al, 2000b) and collagen type IV autoantibodies (Nicoloff et al, 2002).…”
Section: Introductionmentioning
confidence: 99%